METHODS OF MATHEMATICAL STATISTICS AS A MEANS OF PROFESSIONAL COMPETENCE FORMATION OF STUDENTS-ECOLOGISTS - S. I. Toropova (Russian State Vocational Pedagogical University, 2018)
Introduction. Today, the worsening conditions of the human habitat are generating considerable interest in terms of the active development of the system of ecological education and education of the population. Special requirements in modern conditions are imposed to the qualification and competence of environmental professionals: to possess the skills for independent collecting reliable ecological information and to be able to analyze it by means of rigorous mathematical calculations; to perform necessary measurements and calculations within observations and experiments; to choose and to competently realize an adequate algorithm or a mathematical method for the solution of a specific ecological task; to make evidence-based forecasts of changes of environmental conditions. The aim of this publication is to reveal the potential of mathematical statistics methods application for the professional competencies formation of future ecologists. Methodology and research methods. Methodological framework of the research is made up of a competency-based approach to the preparation of high school specialists. The analysis of existing regulations and academic material sources focused on application of mathematical statistics methods for future ecologists' training was carried out. The experience of such training in different universities of Russia was summarized. Results and scientific novelty. The main methodological and organizational problems in the training of environmental students in statistical data analysis are revealed: orientation of the existing training programs and methods of professional education towards the "average" student; insufficient quantity of professionoriented study guides; large volume of statistical information, necessary for studying, and limitation of temporary opportunities for its understanding and evaluation; a lack of future ecologists' experience on application of mathematical statistics toolkit; etc. The conditions for the solution of these problems are planned: careful selection of professionally significant content of the academic discipline "Mathematics"; providing an optimum balance between mathematical tasks and theoretical material; training of students in competent interpretation of the received mathematical results in the context of ecology; efficient use of software in educational process. A number of the general methodical provisions which should be observed in mathematical statistics teaching are formulated to achieve a positive effect. The importance of a regional component of professional training of ecologists is emphasized. Detailed consideration of using the system of specially formulated tasks of a professional environmental orientation, in particular, based on official material sources on monitoring data of the Kirov region environment, is given. The possible directions of students' independent research work organization in the study of mathematical statistics are presented. The ways for providing and strengthening of interdisciplinary and intersubject relations are highlighted. Practical significance. The results of the study can be used to improve the content of the academic discipline "Mathematics" included in education programs for ecological specialties.